(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Reproductive function is one of the most significant areas of human life. The biological meaning of sexuality as a manifestation of the reproductive function lies in the fact that it ensures the permanent preservation of humanity as a species, and all basic human needs are connected to it to one degree or another. Therefore, sexual disorders affect not only the narrow area of biological reproduction, but to one degree or another the entire environment of human existence. Sexuality explicitly or latently affects the course of activity and mental processes in all other spheres of human activity, even in those that are formally very far from reproductive behavior proper.